EFFECTIVENESS OF Sargassum sp EXTRACT IN REDUCE BLOOD SUGAR LEVELS AND ACCELERATE WOUND HEALING ON THE SKIN OF DIABETES MELLITUS MICE (Rattus novergicus) - Kaihena, Martha; Umagapi, Muhammad Cesar; Kaliky, Arief Rahman Shabri; Tarangi, Filep Marfil; Ukratalo, Abdul Mahid (Universitas Pattimura, 2024)
Diabetes Mellitus is a metabolic disorder characterised by elevated blood sugar levels beyond normal ranges, resulting from reduced secretion of the hormone insulin by pancreatic β cells and/or impaired insulin action. Diabetes therapy is often overseen by regulating blood glucose levels regularly and preventing or reducing the risk of complications. Sargassum sp is a variety of brown seaweed native to Indonesia with possible antioxidant and antidiabetic properties. This study seeks to evaluate the efficacy of Sargassum sp extract in lowering blood sugar levels and speeding up wound healing on the skin of diabetic mice. This is an experimental study that uses mice as experimental subjects. The mice were categorised into 5 groups (K-, K+, P1, P2, and P3). Their initial blood sugar levels were recorded, a skin incision was performed, and STZ was administered. When blood sugar levels rise, the K+ group receives metformin; on the other hand, P1, P2, and P3 are administered Sargassum sp extract at a specified dosage. The data were examined using ANOVA and SPSS. The analysis revealed that the water content of Sargassum sp was 4.32%, and the yield value of the concentrated extract was 8.75%. The ethanol extract of Sargassum sp has been revealed to lower blood sugar levels and speed up the wound healing process in mice with diabetes mellitus. The effects observed include decreased blood sugar levels and enhanced wound healing percentage, which are dose-dependent.